2012
DOI: 10.1103/physreva.86.043808
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous derivation of the triple scattering signal from single-atom responses

Abstract: We study coherent backscattering of intense laser light from three immobile two-level atoms using the master-equation approach. The master equation is solved analytically, and the triple scattering spectrum is expressed in quadratures. We show that this solution can be obtained via a self-consistent combination of single-atom spectral responses, and is equivalent to the solution following from the diagrammatic pump-probe approach. We deduce the general expressions for single-atom building blocks which can be u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 33 publications
(141 reference statements)
3
17
0
Order By: Relevance
“…Recently, it has been shown that there is a systematic way of obtaining analytical expressions for such blocks in case of an arbitrary number of probe fields [19]. In future work, these expressions will be incorporated into the theory of nonlinear transport by classical scatterers [27] to describe CBS of intense laser light in cold atomic gases [17].…”
Section: The Diagrammatic Pump-probe Approach For Two-level Atomsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, it has been shown that there is a systematic way of obtaining analytical expressions for such blocks in case of an arbitrary number of probe fields [19]. In future work, these expressions will be incorporated into the theory of nonlinear transport by classical scatterers [27] to describe CBS of intense laser light in cold atomic gases [17].…”
Section: The Diagrammatic Pump-probe Approach For Two-level Atomsmentioning
confidence: 99%
“…III E 1, that pairs of circles correspond to the factorized parts of the atomic dipole correlation function, which describe the elastic spectral responses. The number of pairs of circles in the graphical expansion of the building blocks is equal to 2 n , where n is the number of incoming probe fields [19,24]. Apart from the open circles, each of the graphical equations in Figs.…”
Section: B Diagrammatic Expansion Of the Double Scattering Processmentioning
confidence: 99%
See 3 more Smart Citations